Impact of the curriculum and the micro-curriculum of the Modern Languages Program at the University of San Buenaventura in the oral production skills in FFL among fourth-semester and eighth-semester students (2022)
The present study investigated the effect of the curriculum and French micro-curriculum among fourth-semester and eighth-semester students from the Modern Languages Program at the University of San Buenaventura. Eleven students answered a thirteen-question survey regarding their French development and issues. Consequently, three sessions of French-speaking classes were observed, where the professors selected five students from each semester to be study subjects of the research. Our analysis showed that most students consider that vocabulary is their main problem in French and their level does not meet the level required for their semester; students are not participating constantly in class; they are not practicing a lot of their French at home, which makes the foreign language acquisition process slower. We conclude that to improve participation and oral production in French, professors should concentrate on vocabulary with more ludic and dynamic activities to motivate the students to learn the foreign language and keep them engaged with the class.